2013
DOI: 10.1038/srep02761
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Q-Bands of the Chlorophylls: Coherence Loss via Qx − Qy Mixing

Abstract: We provide a new and definitive spectral assignment for the absorption, emission, high-resolution fluorescence excitation, linear dichroism, and/or magnetic circular dichroism spectra of 32 chlorophyllides in various environments. This encompases all data used to justify previous assignments and provides a simple interpretation of unexplained complex decoherence phenomena associated with Qx → Qy relaxation. Whilst most chlorophylls conform to the Gouterman model and display two independent transitions Qx (S2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
274
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(298 citation statements)
references
References 46 publications
23
274
1
Order By: Relevance
“…52,53 While it has been shown that internal coordinate system yield better results for the vibronic equations due to the fact that there are less coordinates displaced versus the Cartesian system, some of the same researchers have produced significant work and comparisons in Cartesian coordinates. 54,55 In addition to comparisons between the adiabatic and vertical Hessian. 56 It should be noted that an internal coordinate system is many times preferred, but not as widely available.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…52,53 While it has been shown that internal coordinate system yield better results for the vibronic equations due to the fact that there are less coordinates displaced versus the Cartesian system, some of the same researchers have produced significant work and comparisons in Cartesian coordinates. 54,55 In addition to comparisons between the adiabatic and vertical Hessian. 56 It should be noted that an internal coordinate system is many times preferred, but not as widely available.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…In the harmonic approximation to the ground-state and excited-state potential energy surfaces, if the form of the normal modes does not change then the bandwidth for photoemission corresponds to that for photoabsorption, a commonly good approximation in molecular spectroscopy but one that can also fail badly, e.g., for chlorophylls. [92][93] In practice, reorganization energies become susceptible to vibronic coupling effects that can dramatically change the shapes of excited-state potentialenergy surfaces. This occurs as the influence of vibronic coupling depends strongly on the energy gaps between excited states, demanding global accuracy across the excited state manifold if computational methods are to satisfactorily predict absorption and emission bandwidths.…”
Section: Widths Of Photoabsorption and Photoluminescence Spectramentioning
confidence: 99%
“…It can also be extended to multi-mode multi-state problems including modes of different symmetry [27] (e.g., the electrochemical, spin resonance, electronic spectroscopy, vibrational spectroscopy, Stark spectroscopy, etc., of the special-pair radical cation in bacterial photosynthesis can be quantitatively modelled [47,49] in quick time using a 70-mode 4-state model [50], the Q-band spectra of the chlorophyllides can be fitted using a real-time algorithm involving 52 modes and 2 states [55], etc.). However, solution of the problem using Born-Oppenheimer basis functions is intrinsically unstable, requiring vibrational basis sets with dimensions found to scale empirically as conical intersections are approached as This general requirement for the convergence of any numerical calculation of full quantum dynamics performed using the Born-Oppenheimer representation immediately tells that the diagonal correction is globally important.…”
Section: Lmentioning
confidence: 99%
“…Simple models can also be extended to universal quantitative ones provided that full quantum solutions [26,50], sufficient interfering processes [43,[51][52], and motions orthogonal to the reaction coordinate are also included [27,[53][54]. The assignment [55] of the Q-band spectrum of chlorophyll-a, arguably the world's most important chromophore whose properties display a strong pseudo-Jahn-Teller effect, following 50 years of intense debate, provides another example of the power of this approach.…”
Section: Related Contentmentioning
confidence: 99%